Urbanização e planejamento da Amazônia: diálogos com Bertha Becker - Eudes Leopoldo (Confins)
The aim is to understand the urbanization and planning of the Amazon based on the contributions of Bertha Becker. In the first moment, the urban phenomenon is considered from the Amazon in the books published in the 1980s and 1990s by Bertha Becker: "Geopolitics of the Amazon: the new frontier of natural resources" from 1982 and "Amazon" from 1990. In the second moment, the urbanized forest is discussed, based on the following publications by the author: "Amazon - geopolitics at the turn of the III millennium" from 2004 and "The Amazon city - the forest and the city" from 2013. The aim is to highlight Bertha Becker's contributions on the production of cities, the diffusion of the urban and planning in the Amazon to seek to develop, comparing this bibliographical research with recent ongoing processes, new interpretations about urbanization and metropolization in this region and its trends.